Edible bird’s nest mitigates histological alterations in the cortexes of rats’ brains subjected to lead toxicity - Albishtue, Abdulla A.; Yimer, Nurhusien; Zakaria, MD Zuki A.; Haron, Abd Wahid (ResearchersLinks, 2024)
Lead (Pb) is a heavy metal which possesses a long half-life and a distinct negative effect on the bodies of humans and animals. Lead precipitates in various tissues of the body, especially the central nervous system, which causes histological structural changes that may persist even after its concentration in the blood reduces. It produces neurotoxicity related to the deterioration of brain functions. Edible bird’s nest (EBN) is important natural product that has biological characteristics, such as regenerative effect. The objective of this research was to evaluate EBN’s neuroprotective role on the cerebral and cerebellar cortexes of lead acetate-exposed adult female rats. Thirty Sprague Dawley rats were allocated randomly into five groups, with six rats in each group. The control group (C) received solely distilled water. Meanwhile, the treatment groups (T0, T1, T2, and T3) received lead acetate (LA) at a dose of 10 mg/kg BW along with increasing doses of EBN at 0, 30, 60, and 120 mg/kg BW each day, respectively, for five weeks. Behavioural changes were monitored in the various groups. Blood sample for measurement of redox status markers (thiobarbituric acid reactive substances (TBARS) and total antioxidant capacity (TAC)) and brain tissue samples for histopathology, were collected after euthanization. Aggression, loss of appetite and uncoordinated body movement were increased in T0 group and absent in the T3 group. Rats pre-treated with EBN showed reduced LA -induced alteration in brain histology and apoptosis attributed to increased TAC and decreased lipid peroxidation (TBARS). These results suggest that EBN’s anti-apoptotic, proliferative, and antioxidant properties lessen the neurotoxicity caused by lead acetate.